An Empirical Study on Marketing Prospecs and Potential of Steel Industry in India - Bagla, Varun (2008)
In this dissertation, a sectoral review of the steel industry in India was taken into consideration. The emphasis was laid down in finding out to know the competitive advantages, which the large Indian Steel Companies have created overtime and their adaptation to the changing environment. I also analyzed the marketing potential and prospects of the steel industry in India. This study focuses on the two major companies in the steel sector in India, namely Steel authority of India ltd (SAIL) and TATA Steel. For the purpose of investigation, both primary as well as secondary source of information was collected to get the results. Many books on the related topic like books on steel marketing, competitive advantage, business research methods etc. were also consulted along with a number of visits to the libraries for research purpose. Related quotes and texts have been mentioned in the literature review section of the report. Successful questionnaires and interview surveys were conducted among the officials of Steel authority of India ltd (SAIL) and TATA Steel in New Delhi in order to know their responses towards the research questions. After all the research work and collection of questionnaires and surveys, I have come to know the various marketing aspects of steel sector in India. This also helped me to know about the various strategies that the companies have adopted to gain competitive advantage.